Antibacterial activity and GC-MS analysis of the Citrus amblycarpa (Hassk) Ochse essential oil - Mulyani, Sri; ., Susilowati; Hutabarat, Maniur (INDONESIAN JOURNAL OF PHARMACY, 2009)
A research about anti-bacterial activity and components of essential oil from leaves and peels of Citrus amblycarpa have been done.The components of essential oil had been identified by using GC-MS and anti-bacterial activity against S. aureus ATCC 25923 and E. coli ATCC 25922 had been determined with liquid dilution method. The component of essential oil from leaves that can be identified are Î²-pinene, linalool, citronellal, citronellol and geraniol, while from peels are Î²-pinena, cymene, limonene and citronellal.Oil from the leaves has stronger anti-bacterial activity against S. aureus than from peels. On the other hand oil from peels is stronger anti-bacterial activity against E coli.Key words : Citrus amblycarpa, essential oil, anti-bacterial activity.